Culture or commerce - Helsloot, John (Traditiones (Ljubljana), 2012)
This article focuses on the practical effects of ethnology's framing of ritual. It examines the attitude of Dutch municipalities towards subsidizing the annual St. Nicholas parade. Some are in favor, considering the parade an element of tradition. Others are opposed, arguing that the parade is a commercial activity. Because the parade, and much other ritual, has both cultural and commercial facets, the author encourages ethnology to design a more fitting, encompassing concept.
Keywords: ethnology; Etnologija; customs; Šege; Miklavževanje; Netherlands; Nizozemska; ljudske šege; ljudski prazniki